Can Service Climate Detract from Employee Performance? The Role of Experience in Optimizing Satisfaction and Performance Outcomes. (18th November 2016) - Gabler, Colin B.; Rapp, Adam; Richey, Robert Glenn; Adams, Frank G.
ABSTRACT: In this research, we test the curvilinear relationships between service climate perceptions and two employee performance outcomes. Specifically, we propose that while service climate can be beneficial, high levels can actually be detrimental to customer satisfaction and sales performance. Additionally, we propose that a global assessment of employee experience that captures knowledge, skills, and abilities, or KSAs, moderates these curvilinear relationships by providing a means to balance outcome goals. We test our theory using data obtained from 312 employees in a service setting, which we pair with their managers' assessments of their sales performance as well as satisfaction ratings from their customers. Our results reveal two things: (1) an inverted U‐shaped relationship between service climate and sales performance and (2) the level of experience moderates the relationship. These findings suggest that more experienced employees are better able to adjust behaviors to achieve high levels of performance than less experienced employees. Based on these results, we offer theoretical implications and applications for managerial practice.